Do dogs (Canis lupus familiaris) make counterproductive choices because they are sensitive to human ostensive cues? - S. Marshall Pescini; C. Passalacqua; M. E. Miletto Pedrazzini; E. Prato Previde; VALSECCHI, Paola Maria (PLoS ONE, 2012)
Dogs appear to be sensitive to human ostensive communicative cues in a variety of situations, however there is still a measure of controversy as to the way in which these cues influence human-dog interactions. There is evidence for instance that dogs can be led into making evaluation errors in a quantity discrimination task, for example losing their preference for a larger food quantity if a human shows a preference for a smaller one, yet there is, so far, no explanation for this phenomenon. Using a modified version of this task, in the current study we investigated whether non-social, social or communicative cues (alone or in combination) cause dogs to go against their preference for the larger food quantity. Results show that dogs’ evaluation errors are indeed caused by a social bias, but, somewhat contrary to previous studies, they highlight the potent effect of stimulus enhancement (handling the target) in influencing the dogs’ response. A mild influence on the dog’s behaviour was found only when different ostensive cues (and no handling of the target) were used in combination, suggesting their cumulative effect. The discussion addresses possible motives for discrepancies with previous studies suggesting that both the intentionality and the directionality of the action may be important in causing dogs’ social biases.